Pengaruh Citra Merek, Kualitas Produk, Dan Persepsi Harga Terhadap Keputusan Pembelian Sepatu Adidas Di PASI (Persatuan Atletik Seluruh Indonesia) Kabupaten Bangka - Vera Vera; Dhian Tyas Untari; Andrian Andrian (Universitas 45 Surabaya, 2024)
This research aims to research, test and assess the influence of the independent variables Brand Image, Product Quality and Price Perception on the dependent variable Purchase Decision for Adidas PASI athlete shoe products in Bangka Regency. The sample in this study was 107 athletes. This type of research uses a quantitative approach. Data was collected directly from respondents using research instruments in the form of questionnaires via Google Form and purposive sampling techniques. then the data results were processed using the SPSS 23 data processing application. The results of this research prove that Brand Image and Price Perception have a positive and significant effect on the Purchase Decision for Adidas shoe products partially. Meanwhile, product quality has no partial effect on the decision to purchase Adidas shoes. However, this research proves that brand image, product quality and price perception have a positive and significant influence on decisions to purchase Adidas shoe products simultaneously.